ROMANESQUE AND GOTHIC STYLES IN ARCHITECTURE (ON THE EXAMPLE OF ANCIENT ROME) - Sunnatov T. R. (Western European Studies, 2024)
This article discusses the influence of artistic creativity on our way of life and its impact on the development of art in our country. In addition, what is artistic creativity itself? How does it enter our lives? Does it only have a negative effect or, on the contrary, a positive one? The article seeks to help find answers to these questions
Keywords: creativity; artistic creativity; style; direction